2007
DOI: 10.1056/nejmoa062382
|View full text |Cite
|
Sign up to set email alerts
|

A Human Interleukin-12/23 Monoclonal Antibody for the Treatment of Psoriasis

Abstract: This study demonstrates the therapeutic efficacy of an interleukin-12/23 monoclonal antibody in psoriasis and provides further evidence of a role of the interleukin-12/23 p40 cytokines in the pathophysiology of psoriasis. Larger studies are needed to determine whether serious adverse events might limit the clinical usefulness of this new therapeutic target. (ClinicalTrials.gov number, NCT00320216 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
520
1
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 728 publications
(548 citation statements)
references
References 32 publications
13
520
1
14
Order By: Relevance
“…Recently, the therapeutic effect of an IL-12/ IL-23 monoclonal antibody has been demonstrated in psoriasis (24). Our findings suggest that the IL-23 pathway may also be a promising target for treatment of AS.…”
Section: Discussionsupporting
confidence: 51%
“…Recently, the therapeutic effect of an IL-12/ IL-23 monoclonal antibody has been demonstrated in psoriasis (24). Our findings suggest that the IL-23 pathway may also be a promising target for treatment of AS.…”
Section: Discussionsupporting
confidence: 51%
“…Understanding the complex, pleiotropic action of IL-23R and the specific variants that give rise to each of these autoimmune traits will undoubtedly increase progress in our understanding of the molecular pathophysiology underlying these chronic autoinflammatory conditions. Moreover, coupled with the recent advances in autoinflammatory biology, the IL23R variants described herein may lead to a deeper understanding of molecular action of targeted therapeutics such as the efficacious IL-12/IL-23 monoclonal antibodies [44][45][46] and prove useful in autoinflammatory pharmacogenetics.…”
Section: Discussionmentioning
confidence: 98%
“…In sum, these studies demonstrate several key aspects of IL-23/T H -17 pathobiology related to psoriasis: (1) Both IL-12p40 and IL-23p19 mRNA expression levels are significantly elevated in both nonlesional psoriatic skin versus normal skin as well as lesional psoriatic skin versus non-lesional psoriatic skin. 37,38 (2) (5) clinical studies have shown dramatic efficacy of IL-12p40 antibodies in reducing symptoms in a high percentage of psoriatic subjects 44,45 and those with active Crohn's disease. 46 These diverse studies have conspired to highlight the central function of the IL-23/T H -17 axis in mediating chronic inflammatory disease pathogenesis, downplaying the role of IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…KC-derived IL-1β, IL-6, and TNF-α and pDC-derived IFN-α are thought to activate local dDCs, leading to IL-23 secretion to prime naive T cells into 1 and/or 17 sets in dLNs [4,60]. Recently, the signi cance of IL-23/ IL-17/IL-22 axis in psoriasis has become more evident from genome wide studies, the e cacy of biologics targeting these cytokines, and reduction in these cytokines a er disease amelioration [61,62,63]. It has attracted the attention again which DC subsets play a pivotal role in producing IL-23 and in [64,65].…”
Section: Dermismentioning
confidence: 99%